O reconhecimento das Necessidades de Saúde de familiares e crianças egressas da terapia intensiva neonatal: potencialidades e desafios para a continuidade no seguimento ambulatorial - Andreza Miranda de Abreu (2016)
The recognition of the health needs of families and children recent grads of the neonatal intensive care unit: the potential and challenges to continue in the follow-up. 2016. Dissertation (Master's Degree in Health and Nursing) - Nursing College, Minas Gerais Federal University, Belo Horizonte, 2016. The Children With Special Health Care Needs (CRIANES) are those which are in increased risky to develop a chronic condition related to their own development, to the behavioral or emotional conditions and that have the necessity in using health services more than other kids. From this perspective, the professional has a fundamental role in the follow-up, and his comprehension about the CRIANES health needs may interfere on the quality of the care accomplished as well as on the care continuity. Objective: analyzing, under the professional's perspective, health needs of Children With Special Health Care Needs and their relatives in an ambulatory segment. Methodology: it was done an exploratory qualitative studying with the methodological referential dialectic and Agnes Heller's theoretical referential, in which the author writes about the necessities on the social relationships. The fieldwork was made in an ambulatory specialized in child health in a philanthropic hospital localized in Belo Horizonte. The participants were nine workers from the multi professional team. The data were collected by interviews with the workers utilizing a semi structured script and by field observing, where was observed the path made by the relative and/or caregiver on his son's appointment day. It was done an external validation with the professionals, where was exposed to them the synthesis of the results and through a script their impressions were registered. The data analyzing was supported by Bardin's content theme and from it appeared four different empirical categories: "The Health Needs different dimensions under the professionals perspective in the follow-up"; "Health necessities and the CRIANES social context"; "Interactions between professionals, relatives and CRIANES in the follow-up context"; "The moment when the CRIANES relative and/or caregiver meet the professionals: Health needs which reveal themselves". This analysis revealed that the professional workers, through their narratives, recognized health needs in the CRIANES and their families care contexts, the relationship that exists with the social context where they live and that these relationships are demonstrated by the CRIANES relative and/or caregiver in their contact with work. It can be concluded that the health needs implementation showed itself as a knowledge that came to strengthen the professional practices. In this ambulatory, the workers do not discuss systematically about the cases. Then, it becomes really important to think in strategies to improve the articulation between the team and between the assistance levels to not let the health needs acknowledgment by the team be compromised.